2001
DOI: 10.1603/0022-0493-94.5.1122
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Adult Hymenopteran Parasitoids of the Nantucket Pine Tip Moth (Lepidoptera: Tortricidae) to Broad-Spectrum and Biorational Insecticides in a Laboratory Study

Abstract: Currently, there is an elevated interest in reducing feeding damage caused by the Nantucket pine tip moth, Rhyacionia frustrana (Comstock), a common regeneration pest of loblolly pine, Pinus taeda L. The toxicity of several insecticides was tested in a laboratory against four common R. frustrana parasitoids. There were no differences in parasitoid mortality between the control and indoxacarb treatments. However, the pyrethroids, permethrin and lambda-cyhalothrin, caused significantly more mortality initially (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Indoxacarb, the Þrst commercial insecticide of the pyrazoline class, has strong Þeld activity against Lepidoptera that attack vegetables, fruit tree, vines, cotton, corn, and other crops, and a key feature is its novel bioactivation: it blocks the insect voltage-gated sodium channel by the N-decarbomethoxyllated metabolite (Wing et al 1998(Wing et al , 2000Silver and Soderlund 2005). Some studies have reported that this insecticide is safe for natural enemies (Nowak et al 2001, Yu et al 2009). Many studies showed that B. thuringiensis are harmless to Trichogramma species (Antonio et al 2001, Zhu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indoxacarb, the Þrst commercial insecticide of the pyrazoline class, has strong Þeld activity against Lepidoptera that attack vegetables, fruit tree, vines, cotton, corn, and other crops, and a key feature is its novel bioactivation: it blocks the insect voltage-gated sodium channel by the N-decarbomethoxyllated metabolite (Wing et al 1998(Wing et al , 2000Silver and Soderlund 2005). Some studies have reported that this insecticide is safe for natural enemies (Nowak et al 2001, Yu et al 2009). Many studies showed that B. thuringiensis are harmless to Trichogramma species (Antonio et al 2001, Zhu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Spinosad, its active ingredient, causes paralysis by activation of the nicotinic acetylcholine receptors (Tomlin 2000). It was found to be toxic to heteropterans (Studebaker and Kring 2003;Myers et al 2006), some hymenopteran parasitoids (Nowak et al 2001), staphylinid beetles, and earwigs (Cisneros et al 2002). It has, however, little negative effect on the survival or reproduction of predatory mites, Harmonia coccinellids (Musser and Shelton 2003), Deraeocoris bugs (Kim et al 2006), Picromerus bugs (Mahdian et al 2007), and braconid wasps (Vargas et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…According to [84], pymetrozine has less of an effect than pirimicarb on aphid natural enemies. Indoxacarb has been shown to be less toxic than lambda-cyhalothrin to arthropod predators and parasitoids [85,86], but its potential hazard to honey bees could be high [87]. Relatively low side effects from pirimicarb against natural enemies have also been recorded [88].…”
Section: Discussionmentioning
confidence: 99%